(untitled) (Docentes 2.0 Journal, 2023)
With the study, it was intended to make a brief of the main postgraduate programs offered in Mexico, related to the communications sector since this information was not concentrated in any other previous document. The objective was to analyze the higher-level programs taught in communication sciences in Mexico. This essay is framed under the deductive method, humanist paradigm, qualitative approach, and descriptive and narrative design. In the 2021-2022 school year, 61,996 students are registered in areas of communication sciences (1.2% of the total number of students in the nation’s higher level), of which 60,722 are studying for a degree (97.95%, 49 specialty (0.08%), 1,149 master’s degrees (1.85%), and 77 doctorates (0.12%). With this information, Mexican universities can carry out better planning to anticipate their enrollment in the area of communications in the next school cycles; in addition, the country has assured professional cadres in the medium term to analyze and transmit information in the different communication media. In the 2021-2022 school year, the Autonomous University of Tamaulipas, Universidad Iberoamericana, Universidad Anáhuac, and Universidad Americana de Europa registered students in their doctoral programs in communications with 5, 29, 26, and 17 students, respectively, the first public and the next three individuals; At the master’s level, 77.3% of students are enrolled in private universities; which shows the predominance of these in postgraduate studies. At the undergraduate level, 44.5% are registered in private universities, and the remaining 55.5% in public universities.